Quantitative Estimation of Cr and Pd in Heteropneustes Fossilis Fish due to Absorption from Tannery Waste Water (Journal of Scientific Research, 2018)
The objective of this research is to reveal the pollution level and its impact on fresh water fish and finally, to estimate the concentration (ppm) of toxic metals chromium (Cr) (53.9 ppm) and lead (Pb) (13.2 ppm) in raw waste water (100%) and in fish (heteropneustes fossilis) (Cr 3.4 ppm, and Pb 2.0 ppm) by Atomic Absorption Spectrometry (AAS). Fresh tannery effluent is collected from Hazaribag-Dhaka and as early as possible some physico-chemical parameters of that effluent such as Electrical Conductivity (EC) (535 ms/cm) and pH (6.1), Total Dissolved Solids (TDS) (30336 ppm), Dissolved Oxygen (DO) (2.0 ppm), Chemical Oxygen Demand (COD) (9480 ppm) are determined. Pisi-culture is done by constructing some pilot base fresh water systems in the laboratory and it has been found that in raw waste water (100%), the fish survival rate is only a few hours (5h), where in rest of others such as 75%, 50%, 25% and 5% waste water systems, the survival rate of fishes is longer than a week after increasing the amount of DO artificially. So, if fishes are eaten from nearby fresh water bodies of Hazaribag-Dhaka, ultimately it may harm the normal physiology of human.